Stress as a seizure precipitant: Identification, associated factors, and treatment options. (January 2017) - McKee, Heather R.; Privitera, Michael D.
Highlights: We summarize the literature on stress and seizures and corresponding treatment trials. Depression and anxiety are higher in patients with stress-triggered seizures, with anxiety as an independent influential factor. Small prospective trials using general stress reduction show promise in improving outcomes in patients with epilepsy. Future research should clarify mechanisms of stress-seizure relationship and establish evidence-based treatment recommendations. Abstract: Stress is a common and important seizure precipitant reported by epilepsy patients. Studies to date have used different methodologies to identify relationships between epilepsy and stress. Several studies have identified anxiety, depression, and childhood trauma as being more common in patients with epilepsy who report stress as a seizure precipitant compared to patients with epilepsy who did not identify stress as a seizure precipitant. In one survey study it was found that a majority of patients with stress-triggered seizures had used some type of stress reduction method on their own and, of those who tried this, an even larger majority felt that these methods improved their seizures. Additionally, small to moderate sized prospective trials, including randomized clinical trials, using general stress reduction methods have shown promise in improving outcomes in patients with epilepsy, but results on seizure frequency have been inconsistent. Based on these studies, we recommend that when clinicians encounter patients who report stress as a seizure precipitant, these patients should be screened for a treatable mood disorder. Furthermore, although seizure reduction with stress reduction methods has not been proven in a randomized controlled trial, other important endpoints like quality of life were improved. Therefore, recommending stress reduction methods to patients with epilepsy appears to be a reasonable low risk adjunctive to standard treatments. The current review highlights the need for future research to help further clarify biological mechanisms of the stress-seizure relationship and emphasizes the need for larger randomized controlled trials to help develop evidence based treatment recommendations for our epilepsy patients.